Mempelajari Laju Kerusakan Krim Kunyit - Lidah Buaya (Curcuma domestica Val. - Aloe vera) pada Berbagai Konsentrasi Phenoxyethanol selama Penyimpanan - Azizah, Alfina Via; Mulyani, Sri; Suhendra, Lutfi (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 9 No 3 (2021): September, 2021)
This study aimed to: 1) Determine the effect of  phenoxyethanol concentrations as a preservative of turmeric-Aloe vera cream. 2) Determine the right phenoxyethanol concentration to produce turmeric-Aloe vera cream with a longer self life and  fulfil the requirement of SNI. This study used a Simple Linier Regression. T he concentration of phenoxyethanol treatment consisted of 6 levels, namely 0% ; 0,2% ; 0,4% ; 0,6% ; 0,8% and 1% . Each treatment was repeated 3 times, so that 18 experimental units were obtained. The data was analysed using linier regression to showed the damage rate of turmeric -Aloe vera cream during storage. The variables observed in turmeric -Aloe vera cream are homogeneous, pH, specific gravity, viscosity, total phenol, total plate count, and yeast fungus score. The results of the study showed that the best concentrations of phenoxyethanol is 1% : homogeneous, pH 5, specific gravity 1,00130 g/cm 3 , viscosity 10400 cps, total phenol 6,33176 mg GAE/g, ALT 0 koloni/g dan AKK 0 koloni/g and also that is able to keep the physical properties of turmeric -Aloe vera cream in 41-53 weeks and can  inhibits microbial growth until 6 weeks. Keywords : turmeric, Aloe vera , preservative, phenoxyethanol